Epitope Mapping of the Hemagglutinin Molecule of A/(H1N1)pdm09 Influenza Virus by Using Monoclonal Antibody Escape Mutants - Matsuzaki, Yoko; Sugawara, Kanetsu; Nakauchi, Mina; Takahashi, Yoshimasa; Onodera, Taishi; Tsunetsugu-Yokota, Yasuko; Matsumura, Takayuki; Ato, Manabu; Kobayashi, Kazuo; Shimotai, Yoshitaka; Mizuta, Katsumi; Hongo, Seiji; et al. (Journal of virology, 2014)
We determined the antigenic structure of pandemic influenza A(H1N1)pdm09 virus hemagglutinin (HA) using 599 escape mutants that were selected using 16 anti-HA monoclonal antibodies (MAbs) against A/Narita/1/2009. The sequencing of mutant HA genes revealed 43 amino acid substitutions at 24 positions in three antigenic sites, Sa, Sb, and Ca2, which were previously mapped onto A/Puerto Rico/8/34 (A/PR/8/34) HA (A. J. Caton, G. G. Brownlee, J. W. Yewdell, and W. Gerhard, Cell 31:417–427, 1982), and an undesignated site, i.e., amino acid residues 141, 142, 143, 171, 172, 174, 177, and 180 in the Sa site, residues 170, 173, 202, 206, 210, 211, and 212 in the Sb site, residues 151, 154, 156, 157, 158, 159, 200, and 238 in the Ca2 site, and residue 147 in the undesignated site (numbering begins at the first methionine). Sixteen MAbs were classified into four groups based on their cross-reactivity with the panel of escape mutants in the hemagglutination inhibition test. Among them, six MAbs targeting the Sa and Sb sites recognized both residues at positions 172 and 173. MAb n2 lost reactivity when mutations were introduced at positions 147, 159 (site Ca2), 170 (site Sb), and 172 (site Sa). We designated the site consisting of these residues as site Pa. From 2009 to 2013, no antigenic drift was detected for the A(H1N1)pdm09 viruses. However, if a novel variant carrying a mutation at a position involved in the epitopes of several MAbs, such as 172, appeared, such a virus would have the advantage of becoming a drift strain. IMPORTANCE The first influenza pandemic of the 21st century occurred in 2009 with the emergence of a novel virus originating with swine influenza, A(H1N1)pdm09. Although HA of A(H1N1)pdm09 has a common origin (1918 H1N1) with seasonal H1N1, the antigenic divergence of HA between the seasonal H1N1 and A(H1N1)pdm09 viruses gave rise to the influenza pandemic in 2009. To take precautions against the antigenic drift of the A(H1N1)pdm09 virus in the near future, it is important to identify its precise antigenic structure. To obtain various mutants that are not neutralized by MAbs, it is important to neutralize several plaque-cloned parent viruses rather than only a single parent virus. We characterized 599 escape mutants that were obtained by neutralizing four parent viruses of A(H1N1)pdm09 in the presence of 16 MAbs. Consequently, we were able to determine the details of the antigenic structure of HA, including a novel epitope.